2023
DOI: 10.1186/s13000-023-01337-5
|View full text |Cite
|
Sign up to set email alerts
|

Breast implant associated EBV-positive Diffuse Large B-cell lymphoma: an underrecognized entity?

Abstract: Breast-implant associated (BIA) lymphoma is an infrequent type of cancer occurring in the fluid and fibrous capsule around a textured breast implant. Recently, both the 2022 WHO 5th edition classification of Haematological tumours (WHO HAEM5) and 2022 International Consensus Classification of Mature Lymphoid Neoplasms (22ICC), recognized breast implant-associated Anaplastic Large Cell Lymphoma (BIA-ALCL) as a definitive entity, defined as a mature CD30-positive T-cell lymphoma, confined by a fibrous capsule, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…It appears to be a growth induced by a state of regional immunosuppression 13 . Only 60 cases have been described in the literature, mainly in relation to kneeprosthetic replacements, mammary implants 14 and cardiac myxomas 15 as mentioned above. No such circumstances were present in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…It appears to be a growth induced by a state of regional immunosuppression 13 . Only 60 cases have been described in the literature, mainly in relation to kneeprosthetic replacements, mammary implants 14 and cardiac myxomas 15 as mentioned above. No such circumstances were present in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel lymphoma type was reported, the breast implant-associated EBV-positive DLBCL; it has not been determined whether this is a separate entity or can be categorized into the EBV-positive DLBCL group [ 66 ].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…In a porcine model, Jacombs et al observed that textured implants that were injected with Staphylococcus epidermidis produced an average bacterial load that was 20 times higher than that of smooth implants [33]. A correlation between the BIA-ALCL and the Ebstein-Barr Virus has also been hypothesized [34]. In recent times, there has been an increased focus on the genetics of BIA-ALCL, as understanding the alterations underlying the disease process could aid in disease prognosis and customized patient care.…”
Section: Clinical Aspectsmentioning
confidence: 99%